Cultura organizacional e comprometimento dos funcionários do Soleil Suíte Hotel - Ramalho, Márcio Rodrigues (2008)
This study examines the relationship of the types of organizational culture perceived in a business hotel with the nature of the link between individual and organization. This linkage between commitment and organizational culture has been little explored, both national and international, requiring more studies. Thus, the survey was conducted in Soleil Suite Hotel, located on the beach of Ponta Negra, city of Natal, Rio Grande do Norte. The independent variable of the proposed model was represented by the types of organizational culture, while the dependent variable was represented by the four dimensions of commitment. It was used in addition to the correspondence analysis, the arithmetic mean, the Pearson s correlation and the simple regression analysis. The results indicated the existence of relationship of the types of organizational culture with the kind of commitment shown by the officials, where the cultures of Group and Innovative, capable of generating an environment dedicated to the work as a team, the development and professional growth of the employees, as well as the creativity and individual freedom of each one to try new things, encourage the dominance of the dimensions Affective, Affiliative and Normative of the tie person-organization